Quality of Color, Moisture Content, Water Activity and pH Marshmallow Gelatin Candy with Addition of Skim Milk - Amertaningtyas, Dedes; Kurniawan, Wahid; Al Awwaly, Khothibul Umam; Evanuarini, Herly; Widyastuti, Eny Sri; Masyithoh, Dewi (Faculty of Animal Science Universitas Brawijaya, 2024)
Skim milk is added to marshmallows to improve their quality because skim contains protein. This study analyzed the effect of adding skim milk to marshmallow candy made from gelatin in terms of color quality (L, a*, b*), moisture content, water activity (Aw), and pH. The research materials used were gelatin, skim milk powder and sugar. This study was a laboratory experiment a Completely Randomized Design (CRD) method consisting of 3 treatments and 4 replications P0 (0% skim milk and 100% water), P1 (25% skim milk and 75% water), and P2 (50% skim milk and 50% water). The data obtained were analyzed using analysis of variance (ANOVA) and if there was a significant difference, it continued with Duncan's Multiple Range Test (DMRT). The addition of skim milk to marshmallow candy resulted in a highly significant difference (p < 0.01) in moisture content and pH, a significant difference (p < 0.05) in color (L), and no significant difference (p > 0.05) in color (a*, b*), and water activity (Aw). The average value of the L color parameters of marshmallow candy was 83.77-86.90; a* color 2.07-2.40; b* color 10.60-12.10; moisture content 21.04-23.00%; water activity 0.79-0.80 and pH 6.09-6.39. The addition of 25% skim milk is the best treatment for making marshmallows based on beef bone gelatin with the addition of skim milk.